2012
DOI: 10.1104/pp.112.195420
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the R2R3-MYB Transcription Factor TaMYB14 fromTrifolium arvenseActivates Proanthocyanidin Biosynthesis in the LegumesTrifolium repensandMedicago sativa     

Abstract: Proanthocyanidins (PAs) are oligomeric flavonoids and one group of end products of the phenylpropanoid pathway. PAs have been reported to be beneficial for human and animal health and are particularly important in pastoral agricultural systems for improved animal production and reduced greenhouse gas emissions. However, the main forage legumes grown in these systems, such as Trifolium repens and Medicago sativa, do not contain any substantial amounts of PAs in leaves. We have identified from the foliar PA-accu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
122
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(123 citation statements)
references
References 87 publications
1
122
0
Order By: Relevance
“…S3; Supplemental FASTA S2; in the most recent M. truncatula genome Mt4.0v1, contig_238935 is assembled as Medtr4g125520.1). Contig_238935_1 has only one amino acid difference from MtMYB14-2 (AFJ53058.1), which is the M. truncatula ortholog of T. arvense MYB14, a protein that induces PA accumulation in white clover (Trifolium repens) and alfalfa (Hancock et al, 2012). We conclude that contig_238935_1 is a new allele of MtMYB14-2, the single amino acid difference probably being due to the fact that the two genes were cloned from different ecotypes of M. truncatula.…”
Section: Identification Of Mtmyb5 and Mtmyb14mentioning
confidence: 85%
See 2 more Smart Citations
“…S3; Supplemental FASTA S2; in the most recent M. truncatula genome Mt4.0v1, contig_238935 is assembled as Medtr4g125520.1). Contig_238935_1 has only one amino acid difference from MtMYB14-2 (AFJ53058.1), which is the M. truncatula ortholog of T. arvense MYB14, a protein that induces PA accumulation in white clover (Trifolium repens) and alfalfa (Hancock et al, 2012). We conclude that contig_238935_1 is a new allele of MtMYB14-2, the single amino acid difference probably being due to the fact that the two genes were cloned from different ecotypes of M. truncatula.…”
Section: Identification Of Mtmyb5 and Mtmyb14mentioning
confidence: 85%
“…MYB14 is the most closely related MYB to TT2 in M. truncatula, but it was only identified after a reannotation of the genome sequence MT3.5v4 (Young et al, 2011). Hancock et al (2012) reported that overexpression of TaMYB14 (the homolog of MtMYB14 in T. arvense) could induce PA accumulation in leaf tissues of Trifolium spp. and alfalfa, consistent with our result that MtMYB14 is able to promote PA accumulation in M. truncatula hairy roots.…”
Section: Myb5 and Myb14 Physically Interact And Synergisticallymentioning
confidence: 99%
See 1 more Smart Citation
“…TT2-type PA regulators have been characterized in fruit, including DkMYB2 from persimmon (Diospyros kaki), VvMYBPA2 from grapevine (Vitis vinifera), and FaMYB9 in strawberry (Fragaria 3 ananassa; Terrier et al, 2009;Akagi et al, 2010;Schaart et al, 2013). MYBs from the TT2 group also are active in regulating PAs in vegetative tissues, such as LjTT2 from Japanese lotus (Lotus japonicus), TaMYB14 from clover (Trifolium arvense), and MYB134 from poplar (Mellway et al, 2009;Yoshida et al, 2010;Hancock et al, 2012). These MYB transcription factors act as part of the MBW complex that promotes flavonoid gene expression.…”
mentioning
confidence: 99%
“…We have identified TaMYB14 as the regulatory gene from rabbit's foot clover responsible for turning on the genes along the pathway for production of condensed tannins. Silencing the TaMYB14 gene in transgenic plants of rabbit's foot clover blocked the accumulation of condensed tannins (Hancock et al 2012). More importantly, the transgenic transfer of TaMYB14 to white clover and lucerne activated production of condensed tannins in leaves (Hancock et al 2012).…”
Section: Condensed Tannins In Forage Legumesmentioning
confidence: 99%